Women And Fields In The Salako Dayaknese Tribe - Adel, Adellia Alexandra; Dahniar TH Musa; Dwi Surti Junida (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
Salako Dayaknese is one of the Dayaknese sub-tribes in the Sajingan area, Sambas Regency, West Kalimantan. Generally, farming activities in the Dayak tribe are activities that must be carried out by Dayak people to survive and support the family economy. The characteristic of farming owned by the Dayak people, especially the Salako Dayaknese, is that it is cultivated once a year. Hereditary traditions in farming do not seem easy to abandon, although some of them are familiar with modern access systems today, but there are several families who still apply the hereditary farming system from their ancestors. Rukun padi is known to the Salako people as a tradition of planting rice that was passed down by the ancestors. Various rituals and taboos must be followed so that the rice planted can thrive.